2007
DOI: 10.1177/0146167207310454
|View full text |Cite
|
Sign up to set email alerts
|

Mental Exercising Through Simple Socializing: Social Interaction Promotes General Cognitive Functioning

Abstract: Social interaction is a central feature of people's life and engages a variety of cognitive resources. Thus, social interaction should facilitate general cognitive functioning. Previous studies suggest such a link, but they used special populations (e.g., elderly with cognitive impairment), measured social interaction indirectly (e.g., via marital status), and only assessed effects of extended interaction in correlational designs. Here the relation between mental functioning and direct indicators of social int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
165
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(181 citation statements)
references
References 71 publications
10
165
1
5
Order By: Relevance
“…This finding corresponded to work suggesting that even brief social interactions can trigger cognitive resources (as indicated by performance on executive function tasks) that are necessary to maintain smooth social interactions (Ybarra et al, 2008). To the extent that praying is experienced as a social interaction it may thus trigger cognitive resources and facilitate subsequent self-control performance.…”
Section: Discussionsupporting
confidence: 79%
“…This finding corresponded to work suggesting that even brief social interactions can trigger cognitive resources (as indicated by performance on executive function tasks) that are necessary to maintain smooth social interactions (Ybarra et al, 2008). To the extent that praying is experienced as a social interaction it may thus trigger cognitive resources and facilitate subsequent self-control performance.…”
Section: Discussionsupporting
confidence: 79%
“…Second, based on reports that individuals pray to gain subjective strengthening (Janssen et al, 1990), we investigated whether the extent to which individuals try to find strength during praying would mediate the hypothesized effect. Finally, previous research showed that (a) people interpret praying as a social interaction with God (Bremner, Koole, & Bushman, 2011;Schjoedt, Stødkilde-Jørgensen, Geertz, & Roepstorff, 2009), and (b) even brief social interactions can trigger cognitive resources and enhance executive control (Ybarra et al, 2008). We therefore investigated engagement in social interaction as a third potentially mediating factor.…”
Section: Introductionmentioning
confidence: 98%
“…Children growing up with less face-to-face interactions could have difficulty developing relationships with the people they interact with on a daily basis, and could suffer from limited social skills in faceto-face interactions. In addition, there is evidence that participation in social interactions facilitates general cognitive functioning [339].…”
Section: Resultsmentioning
confidence: 99%